2009
DOI: 10.1002/pro.229
|View full text |Cite
|
Sign up to set email alerts
|

How strong are side chain interactions in the folding intermediate?

Abstract: Influence of 12 nonpolar amino acids residues from the hydrophobic core of apomyoglobin on stability of its native state and folding intermediate was studied. Six of the selected residues are from the A, G and H helices; these are conserved in structure of the globin family, although nonfunctional, that is, not involved in heme binding. The rest are nonconserved hydrophobic residues that belong to the B, C, D, and E helices. Each residue was substituted by alanine, and equilibrium pH-induced transitions in apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 48 publications
(40 reference statements)
2
33
0
Order By: Relevance
“…Similarly Dobson (Lindorff-Larsen et al 2004 argues that a small network of hydrophobic contacts defines the native topology in the TSE. Further evidence that the requirement for a nucleus, which involves NLIs and directs the formation of the TSE, is a general feature of the folding mechanism was described by many researchers (Fulton et al 1999;Paci et al 2003;Geierhaas et al 2004;Krantz et al 2004;Sosnick et al 2004;Lappalainen et al 2008;Tsong et al 2008;Samatova et al 2009). …”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 79%
“…Similarly Dobson (Lindorff-Larsen et al 2004 argues that a small network of hydrophobic contacts defines the native topology in the TSE. Further evidence that the requirement for a nucleus, which involves NLIs and directs the formation of the TSE, is a general feature of the folding mechanism was described by many researchers (Fulton et al 1999;Paci et al 2003;Geierhaas et al 2004;Krantz et al 2004;Sosnick et al 2004;Lappalainen et al 2008;Tsong et al 2008;Samatova et al 2009). …”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 79%
“…In the Laboratory of Protein Physics (Institute of Protein Research, Russian Academy of Sciences) a detailed study of apoMb folding was done. The object of the investigation was the kinetics of folding of mutant proteins with substitutions both in the conserved and non conserved positions important for folding [52,53].…”
Section: Conformational State Of Globular Proteins In the Presence Ofmentioning
confidence: 99%
“…Numerous works showed that local and non-local contact are critical for the proper folding in both hierarchical and nucleation-condensation folding models. Studies of various mutants of apomyoglobin of different sources were reported by several groups where contributions of both local and non-local interactions were found [33,[76][77][78][79][80]. Numerous studies of the folding of SH3 domains showed a similar sequence of events where non-local contacts lead to the formation of a nucleus [23][24][25][81][82][83][84][85], and the context dependence of secondary structure formation was also shown [86].…”
Section: The Interplay Of Local and Non-local Interactions In The Folmentioning
confidence: 99%
“…Furthermore, they proposed that protein folding occurs through consecutive looping of the chain, with the loops ending primarily at hydrophobic nuclei. The role of non-local interactions in the early phases of folding pathways was described in many studies [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%